Corporate Social Responsibility: Concept and Experiences - Noknoi, Chetsada (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This article aims at strengthening the understanding of corporate social responsibility, which is a contemporary organizational management concept. It begins with the explanation of the importance and the meaning of corporate social responsibility. It then explains the corporate social responsibility concept. The final part presents the experiences of the organizations that use the corporate social responsibility concept in managing their organizations. If all organizations accept the corporate social responsibility concept and follow it, it would result in constant development.